High‐Performance Stable Perovskite Solar Cell via Defect Passivation With Constructing Tunable Graphitic Carbon Nitride. Issue 8 (11th July 2021) - Ho, Ching-Mei; Wu, Ming-Chung; Chen, Shih-Hsuan; Chang, Yin-Hsuan; Lin, Ting-Han; Jao, Meng-Huan; Chan, Shun-Hsiang; Su, Wei-Fang; Lee, Kun-Mu
Abstract : Organic–inorganic hybrid perovskite solar cell (PSC) demonstrates outstanding photovoltaic characteristics. However, the instability under high temperature and high relative humidity remains an obstacle that needs to be overcome. Furthermore, the rapid growth of perovskite crystals causes a lot of defect formation in the perovskite active layer, leading to insufficient stability. Two‐dimensional g –C3 N4 is a typical lewis base, providing electron pairs for bonding and is suitable as a template for controlling the nucleation of the perovskite active layer. Herein, tunable g –C3 N4 by calcining the precursors (cyanamide, dicyandiamide, and urea) at different conditions to control the grain size and to passivate perovskite crystal is constructed. The Kelvin probe force microscopy study reveals that the successful defect passivation by urea‐polymerized g –C3 N4 (UCN) at grain boundaries could induce the suppression of non‐radiative recombination. Adding the least polymerized UCN into a perovskite film allows for uniform surface morphology and a reduced trap density. UCN coordinated with the perovskite provides an efficient path for electron injection to the electron transport layer. The unencapsulated PSCs with UCN additive achieve a maximum power conversion efficiency of 20.03% and retain ≈93% of their initial efficiency values after aging for 960 h at 25 °C and relative humidity of 30%. Abstract : Herein, the contruction of tunable graphitic carbon nitride ( g –C3 N4 ) into perovskite is introduced. g –C3 N4 is obtained by thermal polymerization from different precursors (dicyandiamide, cyanamide, and urea), which act as a template for modifying the perovskite nucleation rate. Urea‐derived g –C3 N4 reduces the defects of the perovskite layer, improving the stability and boosting the efficiency up to 20.03%.